Double-stranded RNA-binding artificial cationic oligosaccharides stabilizing siRNAs with a low N/P ratio. Issue 7 (31st January 2017) - Hara, Rintaro Iwata; Maeda, Yusuke; Sakamoto, Taiichi; Wada, Takeshi
Abstract : Novel double-stranded RNA (dsRNA)-binding molecules were developed for the effective thermodynamic and biological stabilization of nucleic acids including short interfering RNAs (siRNAs). Abstract : Novel double-stranded RNA (dsRNA)-binding molecules were developed for the effective thermodynamic and biological stabilization of nucleic acids including short interfering RNAs (siRNAs). β-(1→4)-Linked-2, 6-diamino-2, 6-dideoxy-d -galactopyranose oligomers (ODAGals) were synthesized for this purpose, and their binding ability with dsRNAs was evaluated. Fluorescence anisotropy measurements showed the 3mer and 4mer of ODAGals to be strongly bound ( K d < 0.02 μM). The UV melting experiments demonstrated that the binding of ODAGals to dsRNAs proceeded with significant thermodynamic stabilization of the duplexes. Furthermore, the 4mer of ODAGal was clearly revealed to almost completely protect siRNAs with a low N/P ratio ( i.e., N in the oligocationic molecule to P in the siRNA ratio) from cleavage by RNase A. On the basis of these results, ODAGals can serve as promising stabilizers or carriers of dsRNA-based drugs such as RNAi drugs.